CARBONIC INCLUSIONS - Van den Kerkhof A.; Thiery R. (My University, 2001)
The paper gives an overview of the phase relations in carbonic fluid inclusions with pure, binary and ternary mixtures of the system CO2-CH4-N2, compositions, which are frequently found in geological materials. Phase transitions involving liquid, gas and solid phases in the temperature range between -192°C and 31°C are discussed and presented in phase diagrams (PT, TX and VX projections). These diagrams can be applied for the interpretation of microthermometry data in order to determine fluid composition and molar volume (or density).
Keywords: FLUID INCLUSIONS; CARBON DIOXIDE; METHANE; NITROGEN; MICROTHERMOMETRY